(untitled) (Proceedings of Voronezh State University. Series: Geology, 2024)
Introduction: in the vicinity of faults, along which the boundaries of coal mine fields are drawn, thick, insignificant in length and relatively isolated gas-bearing reservoirs are formed, which by their filtration properties approach and sometimes exceed the reservoirs of known gas fields. Methane degassing in them is compensated by deep gas flow along geodynamically active fault fragments. Such formations are considered as anomalous accumulations of methane confined to zones of dynamic influence of faults. The study of such accumulations in the interwell space, as well as the current stress-strain state of the upper horizon of the rock massif, identification of geodynamically active zones is possible with the use of radonometric studies. Methodology: in the field of the mine «Kalinovskaya-Vostochnaya» of Donetsk-Makeevskiy coal-bearing region profile emanation survey was carried out to study the current stress-strain state of the upper horizon of the rock massif and to identify geodynamic zones of influence of faults. The separate content of radon and thoron in the soil air was studied using the scintillation emanometer «Radon» at the area of conjunction of Timoshenko and Frantczusky overthrusts. The values of radon and thoron concentration in soil air, radon-thoron ratio and contrast coefficient of anomalies were calculated. Anomalies of coal gas content anomalies by seams were identified. Results and discussion: plots of changes in values of radon and thoron concentrations, radon-thoron ratio along the profiles were constructed. Areas of increased and decreased values of radon and thoron concentrations were singled out. Maps of distribution of values of radon and thoron concentration, radon-thoron ratio and contrast coefficient of anomalies are constructed. The compression zones with low fault activity were identified, which are characterised by low values of radon content, radon-thoron ratio, anomaly contrast ratio and high values of thoron content. The compression condition is confirmed by increased gas content of coal seams due to anomalously high formation pressure in the coal-rock massif. Conclusion: the areas of high values of radon concentration together with low thoron content, high values of radon-thoron ratio and high contrast coefficient of the anomaly, which are geodynamic zones of stretching of active large discontinuity, are identified in the study area. The areas of low values of radon concentration, radon-toron ratio and contrast ratio together with high values of thoron concentration correspond to compression zones with low geodynamic activity. The zone of positive anomalies of gas content in the area of the Frantczusky overthrust and Timoshenko overthrust interlocking on the earth’s surface is combined with the radonometric compression zone. Anomalously high gas pressure in coal seams, determined by the level of gas content of coals, is associated with the compression zone, identified by radonometric data.